The NEAT Study (Novel ElectroAcupuncture) - Electroacupuncture After Laparoscopic Colon Cancer Resection: Thinking Outside The Box. : Study Protocol (Principles and Practice of Clinical Research, 2021)
Introduction: Colorectal cancer is the second leading cause of cancer-related death in the US; complete surgical resection is the only curative treatment for non-metastatic colorectal cancer (NMCC). Postoperative ileus (POI) frequently increases patient morbidity and healthcare costs. Enhanced recovery after surgery (ERAS) protocol is the standard of care in most institutions and has been shown to reduce postoperative complications, but there is no a completely effective treatment for this condition. Studies suggest that electroacupuncture (EA) can improve gastrointestinal tract function after surgery.Objective: We aim to determine if including EA in the standard treatment of POI decreases the time to the first defecation, enhancing the return of normal bowel function after colon resection for NMCC.Methods: We propose a phase II, single-center, randomized, triple-blinded, sham-controlled trial with two parallel arms and a 1:1 allocation ratio. Patients 40-80 years of age diagnosed with NMCC scheduled to undergo laparoscopic surgery for colon cancer resection will be included. The arms will be EA + standard treatment and sham EA + standard treatment. The standard treatment will follow the ERAS protocol.Discussion: This will be the first randomized clinical trial to evaluate the impact of using EA along with the ERAS protocol for POI. This intervention may reduce patient morbidity and improve healthcare costs associated with the disease.